PENGEMBANGAN E-MODUL MENGGUNAKAN FLIPBUILDER PADA MATERI KEKAYAAN BUDAYA INDONESIA - Riri Addaafiah Febriana; Lina Novita; Nurlinda Safitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to produce teaching material products on Indonesian cultural riches in class IV at SDN Cilangkap 8, Depok City. This product development uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research began by conducting a needs analysis, student analysis, creating a product design, then developing an e-module product, carrying out expert validation, after that conducting a trial of the e-module on Indonesian cultural wealth material. The results of validation research by media experts, language experts and material experts show that the valid e-module using flip builder is very suitable for use by obtaining an average percentage of 97%. At the trial stage, 33 students gave very good responses and were very suitable for use by obtaining an average percentage of 99%. Based on the research results, it can be concluded that the e-module teaching materials using flip builder on Indonesian cultural wealth material developed by this research are proven to be valid, easy and interesting for students to use and are very worthy of study.